Supply, installation, testing & commissioning of electrical system ( MDB &DB) with all necessary accessories for 13 storied Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Edison Power Bangladesh Ltd. Limited to supply, installation, testing & commissioning of electrical system ( MDB &DB) with all necessary accessories for 13 storied Brac University new campus building project.